2021
DOI: 10.1371/journal.pone.0257907
|View full text |Cite
|
Sign up to set email alerts
|

The association between competitor level and the physical preparation practices of amateur boxers

Abstract: Physical training, testing, and monitoring are three key constitutes of athlete physical performance; however, there is a currently a lack of information on the prevalence of such methods in amateur boxing. This study aimed to explore the physical preparation practices of senior elite (SEB) and senior development (SDB) amateur boxers, and to determine whether these practices were discriminated by competitor level. One hundred and one amateur boxers (SEB n = 59, SDB n = 42) were surveyed on their understanding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…No medical diagnosis was done for the conditions studied. As mentioned by Finlay et al and Altaribba-Bartes et al self reported data in boxing might not be always accurate [ 36 , 37 ]. This could be attributed to the criticizing boxing is receiving for being dangerous (coaches want to highlight the numerous benefits of boxing so that more people join the sport) as well as due to the boxer’s mentality to fight through the injury especially before a bout [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No medical diagnosis was done for the conditions studied. As mentioned by Finlay et al and Altaribba-Bartes et al self reported data in boxing might not be always accurate [ 36 , 37 ]. This could be attributed to the criticizing boxing is receiving for being dangerous (coaches want to highlight the numerous benefits of boxing so that more people join the sport) as well as due to the boxer’s mentality to fight through the injury especially before a bout [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned by Finlay et al and Altaribba-Bartes et al self reported data in boxing might not be always accurate [ 36 , 37 ]. This could be attributed to the criticizing boxing is receiving for being dangerous (coaches want to highlight the numerous benefits of boxing so that more people join the sport) as well as due to the boxer’s mentality to fight through the injury especially before a bout [ 36 , 37 ]. What is more, there is the side of boxing that is associated with underground activities and officially recording of any kind is not welcome by some clubs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power is one of the main physical components in all combat sports [35,6] . In a boxing match, power is generated from how fast the punch moves with the strength of the boxer's hand swing [15,10] . A blow that has more power than the opponent can cause the opponent to fall, be knocked out, or cause injury.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of punching power also depends on body weight classification, the heavier the boxer's body, the greater the power produced, although this will result in a lack of punching speed [8] . Then skills such as training experience and how often he participates in competitions also influence a boxer's skills [10] . The last is the type of punch from boxing [22] .…”
Section: Introductionmentioning
confidence: 99%